Analisis Faktor-Faktor yang Mempengaruhi Promosi Karyawan di Kantor Wilayah Telkom (Witel) Makassar - Nasir, Nasir (LPPM STIE KRAKATAU, 2024)
This study aims to analyze the factors that affect employee promotions at the Telkom Regional Office (Witel) Makassar. Using a qualitative approach, this study explores the perspectives of employees and management through in-depth interviews and participatory observations. The research subjects were selected by purposive sampling to ensure the diversity of backgrounds and experiences related to the promotion process. The data obtained were analyzed using thematic analysis techniques to identify patterns and key influencing factors. The results of the study show that employee promotions are influenced by individual competency factors, contributions to the organization, interpersonal relationships, and meritocratic company policies. In addition, external factors such as market dynamics and changes in business strategies also play a role. These findings reveal that there are mixed perceptions among employees regarding fairness in the promotion process, which can affect work motivation. In conclusion, the success of the promotion system at Witel Makassar depends on transparent, objective management, and focusing on human resource development. The research recommendations include the need to strengthen performance evaluation and training systems to increase opportunities for fair and sustainable promotion